Eksplorasi aktivitas enzimatik dari fungi endofit laut serta aplikasinya untuk hidrolisis kitosan: Exploration of enzymatic activity of marine endophyte fungi and its application for chitosan hydrolysis - Budiman, Muhammad Arief; Tarman, Kustiariyah; Hardiningtyas, Safrina Dyah; Nurazizah, Mirah Afiza (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Marine endophytic fungi are fungi associated with tissues of marine organisms, such as seaweed, coral, seagrass, sponges, and sediments in the marine environment. Fungi can produce extracellular enzymes, including cellulase, amylase, pectinase, chitosanase, lipase, and protease. This study aimed to determine the potential of fungal isolates to produce chitosanolytic, cellulolytic, and proteolytic activities for the degradation of chitosan. Marine endophytic fungal isolates were obtained from seaweed, seagrass, and mangroves from the waters of the Sukabumi and Buton Islands, Indonesia. Twenty fungal isolates were screened for enzymatic activity (chitosanolytic, cellulolytic, and proteolytic) using the agar diffusion method to determine the diameter of the clear zone produced. The hydrolysis process was carried out by inoculating the isolates into hydrolysis media containing colloidal chitosan for seven days. The results showed that 12 isolates had chitosanolytic activity, 8 had cellulolytic activity, and 10 had proteolytic activity. Five isolates showed activity against all tested enzymes. Two isolates with codes KVA and BM48A had the highest chitosanolytic clear zone diameter. Isolates were identified by DNA Barcoding as species with strains Trichoderma harzianum KTR3 and Aspergillus sydowii KTR50. The yields of the chitosan hydrolysate were 7.44% and 6.74%, respectively. Meanwhile, the viscosity values produced were 21.1 cP and 9.26 cP and the molecular weight values were 9.06 kDa and 4.47 kDa. The enzymatic activity produced by marine endophytic fungal isolates has the ability to degrade chitosan, as evidenced by the decrease in the viscosity and molecular weight of chitosan.